2004
DOI: 10.1016/s0014-5793(04)00286-8
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic activity of toxic and non‐toxic type 2 ribosome‐inactivating proteins

Abstract: Ribosome-inactivating proteins (RIPs) display adenine polynucleotide glycosylase activity on di¡erent nucleic acid substrates, which at the ribosomal level is responsible for the arrest of protein synthesis. Some type 2 RIPs, namely ricin and related proteins, are extremely toxic to mammalian cells and animals whilst other type 2 RIPs (non-toxic type 2 RIPs) display three to four logs less toxicity. We studied whether a correlation exists between toxicity on cells and enzymatic activity on nucleic acids. All t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 43 publications
3
64
0
Order By: Relevance
“…Inhibition of protein synthesis by RCA I A chain internalized into endothelial cells would also contribute to the reduction in VEGFR-2. 12,13 Down-regulation of VEGFR-2 after binding and internalization of RCA I was followed by loss of patency and cessation of blood flow. Some endothelial cells of tumor vessels underwent apoptosis, as documented by the appearance of activated caspase-3 staining that colocalized with CD31.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition of protein synthesis by RCA I A chain internalized into endothelial cells would also contribute to the reduction in VEGFR-2. 12,13 Down-regulation of VEGFR-2 after binding and internalization of RCA I was followed by loss of patency and cessation of blood flow. Some endothelial cells of tumor vessels underwent apoptosis, as documented by the appearance of activated caspase-3 staining that colocalized with CD31.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether the striking decrease of VEGFR-2 immunoreactivity of tumor vessels after injection of RCA I was due to a selective effect on VEGFR-2 or to a generalized action of RCA I on protein synthesis, 12,17,18 we asked whether similar changes occurred in other endothelial cell membrane proteins, VEGFR-3, CD31, and CD105.…”
Section: Reduction In Vegfr-2 After Rca I: Selectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…1 These proteins consist of two chains, which exhibit complementary properties. 2 The A chain is an rRNA N-glycosidase, which causes depurination of the 28S rRNA in a catalytic manner and thus leads to transcriptional arrest by inhibiting protein synthesis. 3 The B-chain binds to glycan structures and is prerequisite for internalization of the RIP type II molecule.…”
Section: Introductionmentioning
confidence: 99%
“…16 Based on this background, new drugs are needed for the treatment of PDAC. We reasoned that it would be worth investigating 2 , and Martin R Berger the activity of Rpx in PDAC models, because a colorectal cancer liver metastasis model had shown explicit antineoplastic activity. 1 Moreover, the affinity of Rpx for carcinoembryonic antigen (CEA) 5 suggested that neoplasias expressing this glycoprotein might be preferential targets.…”
Section: Introductionmentioning
confidence: 99%